Pengaruh Membaca Al-Qur’an Metode One Day One Juz terhadap Kecerdasan Intelektual pada Ikatan Mahasiswa Muhammadiyah (IMM) Fakultas Kedokteran Universitas Muhammadiyah Sumatera Utara - Adil Pratama Handoyo; Hendra Sutysna (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
The ODOJ (One Day One Juz) method is a program to read the Qur'an with the target of reading one day to finish one juz. The ODOJ method is a breakthrough to get used to reading the Qur'an. Reading the Qur'an repeatedly will improve the brain work. This study aims to determine the effect of reading the Qur'an using the ODOJ method on intellectual intelligence. This research is a comparative analytic study of 2 unpaired groups with a true experimental design with post test only control group design. The research subjects were 40 people who were taken by purposive sampling method. Data analysis used pair t-test and independent t-test. The independent t-test showed the effect of reading the Qur'an on intellectual intelligence which was significant (p=0.000). The sample who read the Qur'an using the one day one juz method had a superior IQ score of 6 people (15%), High Average as many as 6 people (15%), and an average of 8 people (20%). Meanwhile, those who read freely were in the category of 18 people (45%) on average and 5 people (5%). Reading the Qur'an using the one day one juz method has a significant effect on intellectual intelligence. The next research,, it is hoped that there will be an assessment in terms of intellectual intelligence before intervention, as well as providing a longer intervention so that it can describe more objectively.